OFR-39A-94-Vol. 2 Ergonomic Analysis Of Surface Taconite Maintenance Work - Final Report - Volume 2 -Appendices - Appendix A - Human Factors Research Program, U.S. Bureau Of Mines Twin Cities Research Center - U.S. Bureau Of Mines - Mission (The National Institute for Occupational Safety and Health (NIOSH), 1994)
Our mission is help ensure our country has an adequate, dependable supply of minerals and mate al to meet its national security and economic needs at acceptable social, environmental, and economi[c] costs. We do this by promoting and encouraging private enterprise in the development of viable and stable mineral industries through the transfer of innovative extraction, processing, recycling, an environmental technologies; our use of cooperative partnerships with industry, academia, an government; our timely, authoritative worldwide mineral intelligence; our advocacy of public policies based on good science and sound economics.